PREDICTORS OF THE USE OF GASTROPROTECTIVE AGENTS IN PATIENTS USING NSAID IN YOGYAKARTA INDONESIA - Ady Bagus Indrianto; Jarir At Thobari; Agung Endro Nugroho (Indonesian Journal of Pharmacy, 2012)
Non Steroid Anti-Inflammatory (NSAID) is one type of AntiInflammatory  drug  that  is  used  to  treat  pain  in  patients  of osteoarthritis  (OA)  and  rheumatoid  arthritis  (RA).  The  use  of NSAIDs can cause gastrointestinal side effects. To prevent the side effects,  NSAIDs  are  prescribed  in  combination  with gastroprotective  agent  (GPA).  The  aim  of  the  study  is  to determine  the  factors  considered  in  the  GPA  prescription  by  the doctors  in  patients  who  have risk  factors  for  gastric  disorder  due to  NSAIDs  use.  This  study was  performed using  a  cross-sectional observational  design.  The  data  were  collected  retrospectively during  a  period  of  January to December  2010.  The subjects were OA  and  RA  patients  considering  the  inclusion  and  exclusion criteria.  The  data  included  patient  characteristics  (gender,  age, occupation, payment  method, the primary diagnosis),  prescription of NSAID, prescription of GPA, history of gastrointestinal disease, NSAID  prescription  with  corticosteroids,  prescription  with antiplatelet.  The  data  were  processed  descriptively  and quantitatively, and analyzed statistically using chi-square and log. regression with 95% Confidence Interval. The results showed that there  were  correlation  between  some  predictor  factors  with prescription  of  gastroprotective agent.  These  factors  were  women patient,  patient  age of  ≥  65  years,  oxicam  prescribing, diclofenac sodium prescribing, prescribing >1 type of NSAIDs, prescription of NSAID  concomitant  with  corticosteroids,  prescription  of  NSAID concomitant  with  antiplatelet,  patients  with  history  of gastrointestinal, prescribing NSAIDs with duration of ≥ 3 months. Patient  with  a  history  of  gastrointestinal  disease  was  the  most predictor  influential  factor,  with  OR  (odds  ratio)  of  3.6  (95%  CI: 2.79  -  4.66).  Predictor  factor  of  patients  with  a  history  of dyspepsia  possessed  the  highest  OR  {OR=4,29  (CI  95%:  3.23–5.7)}.  It  means  that  patients  with  a  history  of  dyspepsia prescribed  NSAIDs  would  have  greater  risk  of  4.29  times  to  get GPA  prescription  than  patients  without  a  history  of  dyspepsia. Prescribing  NSAIDs  >  1  DDD  (defined  daily  dose)  had  p  value  of 0.777,  which  means  there  was  no  relationship  between  GPA prescription with NSAIDs > 1 DDD prescription.Key  words: Gastroprotective  Agent,  Non-steroid  anti-inflammatory, Osteoarthritis, Rheumatoid Arthritis